2014
DOI: 10.5901/mjss.2014.v5n2p579
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction as a Moderator of the Relationship between Work-Family Conflict and Stress among Female Civil Service Managers

Abstract: The main objective of the study was to investigate job satisfaction as a moderator of the relationship between work-family conflict and stress among female civil serve managers in the education department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The results of the current study are also consistent with the study of both: Abdel-Latif, (2020), Toga, et al, (2014) There is a statistically significant positive relationship between work and family conflict and job satisfaction that has a large percentage of professional pressures, and the existence of differences in the degree of emotional divorce. Linked to gender are number of years of marriage, level of education and income level per month for the study sample.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the current study are also consistent with the study of both: Abdel-Latif, (2020), Toga, et al, (2014) There is a statistically significant positive relationship between work and family conflict and job satisfaction that has a large percentage of professional pressures, and the existence of differences in the degree of emotional divorce. Linked to gender are number of years of marriage, level of education and income level per month for the study sample.…”
Section: Discussionsupporting
confidence: 91%
“…The described actions may be helpful to prevent or reduce WFC and work-related stress outcomes (Sultana, 2012;Toga et al, 2014). Moreover, it is important to consider that not all individuals are able to recover (Sonnentag, 2003) but that they can learn to do it.…”
Section: Workload and Wfcmentioning
confidence: 99%
“…Furthermore, a heavy workload can lead to time pressure and work-family conflict, contributing to job stress (Chung & Kim, 2019;Tuncdogan & Acar, 2019). A study on nurses found that a heavy workload is related to work-family conflict associated with job stress and turnover intentions (Jang et al, 2019).…”
Section: Heavy Workload and Negative Outcomesmentioning
confidence: 99%